Estimation of Sea Surface Current Velocities using AIS Data - Christodoulou, Constantinos; Herodotou, Herodotos; Michaelides, Michalis P. (My University, 2022)
The Automatic Identification System (AIS) provides information for tracking and monitoring vessel activity in real time. The vessel traffic data from AIS includes position coordinates in latitude and longitude, speed and course over ground, the vessel's unique identification number, and many more. In this work, we investigate the use of AIS data for estimating sea surface current velocities in the Eastern Mediterranean sea. Specifically, we apply the dead reckoning technique to compute the difference between the projected position and the true position of a vessel over time, which is mainly attributed on the force of sea surface currents. The estimated sea surface current velocities and directions are compared with the ones provided by the Copernicus Marine ocean product system. The analysis reveals that the dead reckoning technique can be used reliably for estimating sea currents at a very fine granularity, especially in high-traffic and coastal areas, where there is an increased complexity of obtaining accurate results from other sources.
Keywords: AIS data; Sea surface; Dead reckoning; Force; Sea measurements; Estimation; Real-time systems; Complexity theory